Life-span developmental psychology and social-behavioural aging science: need for better liaisons with life course epidemiology in the future - Wahl, Hans-Werner (Longitudinal and life course studies, 2016)
Longevity risk means living longer than predicted. Attempts to understand longevity risk to date have concentrated on single diseases, usually coronary heart disease, and sought explanations in terms of risk factor change and medical innovation. In an opening paper, David Blane and colleagues point to evidence that suggests changes in positive health also should be considered; and that a life course approach can do so in a way that is socially and biologically plausible. Applying this approach to UK citizens currently aged 85 years suggests that life course research should give priority to trajectories across the whole life course and to the social and material contexts through which each cohort has passed. Testing these ideas will require inter-disciplinary and international comparative research. The opening paper is followed by commentaries by Hans-Werner Wahl, Mark Hayward, Aart Liefbroer and Gita Mishra. Finally Blane and colleagues respond to the points raised by the commentators.